2023
DOI: 10.1055/a-2192-0101
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Non-Metastatic Protein B (GPNMB): The Missing Link Between Lysosomes and Obesity

Valentina Bianco,
Dagmar Kratky

Abstract: As a result of an unhealthy diet and limited physical activity, obesity has become a widespread pandemic worldwide and is an important predictor for the development of cardiovascular disease. Obesity is often characterized by a pro-inflammatory environment in white adipose tissue (WAT), mainly due to increased macrophage infiltration. These immune cells boost their lipid concentrations by accumulating the conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Our previous data along with other recent studies have demonstrated increased circulating levels of GPNMB in those with metabolic diseases [13,30,31]. A distinct correlation has been established between GPNMB and obesity, wherein GPNMB plays a protective role, with anti-inflammatory effects preventing the progression of obesity-related metabolic complications [32]. GPNMB can be proteolytically cleaved into a soluble molecule by lysosomal stress [33].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous data along with other recent studies have demonstrated increased circulating levels of GPNMB in those with metabolic diseases [13,30,31]. A distinct correlation has been established between GPNMB and obesity, wherein GPNMB plays a protective role, with anti-inflammatory effects preventing the progression of obesity-related metabolic complications [32]. GPNMB can be proteolytically cleaved into a soluble molecule by lysosomal stress [33].…”
Section: Introductionmentioning
confidence: 71%
“…The soluble GPNMB is suggested to have an opposite effect, stimulating lipogenesis in white adipose tissue (WAT), resulting in a positive correlation between soluble GPNMB and obesity. This explains the important role of this protein in metabolic disorders [32]. Interestingly, some studies showed that transgenic mice that overexpressed GPNMB showed increased bone resorption [34].…”
Section: Introductionmentioning
confidence: 97%